VECU ET DETERMINANTS DE LA VIOLENCE AU TRAVAIL DANS LES ENTREPRISES DE KISANGANI EN REPUBLIQUE DEMOCRATIQUE DU CONGO: EXPERIENCE AND DETERMINANTS OF VIOLENCE AT WORKPLACE IN KISANGANI COMPANIES IN THE DEMOCRATIC REPUBLIC OF THE CONGO. - Malwilo, Ramazani; Musailwa, Kimenya; Mabella, Kimbuani; Bakadianjila, Tshimpanga (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study examines the experience of violence in the workplace. It aims to determine the effects of certain socio-demographic factors on exposure to violence and on how the victim reacts to it. The study also attempts to determine the specific reactions of victims to each type of violence suffered.This article is a follow-up to the study published in 2021 that identified four forms of workplace violence in Kisangani companies: psychological violence, physical violence, moral violence and sexual harassment. Also, the study had shown that faced with violence suffered in the workplace, the victim can resort to different reactions, such as denial, legal action, cooperation, physical defense, discussion, cooperation, avoidance, etc.The data for this study were collected using the survey questionnaire applied to workers in companies operating in Kisangani in DR-Congo. The collected materials were analyzed by the test of the analysis of variance and the Student's t test as well as the study of the multiple linear regression.Results shown that socio-professional category plays a role in exposure to violence at work. Clearly, exposure to violence depends on the hierarchical position of the worker and not on sex and type of company. The same is true for the reactions expressed in relation to the violence suffered. Indeed, the executive workers resort more to the reactions of denial, avoidance, acceptance and discussion, the executing workers refer to the first three reactions. Supervisors come second in terms of the discussion, as they make less use of denial, avoidance and acceptance than the other professional categories.